Manajemen Produksi Program Televisi Berbasis Streaming Pada PT. Centro Riau Mediatama (CERIA TV) Pekanbaru - Moh Agung Wibowo; Ringgo Eldapi Yozani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The development of local broadcasting media in Indonesia continues to progress alongside technological and information advancements. Local television stations, including Ceria TV, play an important role in the Indonesian television industry by offering unique and diverse program offerings. However, they also face fierce competition from national television stations, which have advantages in terms of capital, equipment, human resources, and societal presence.This research aims to study the pre-production, production, and post-production processes of streaming television programs at Ceria TV Pekanbaru. An interpretative approach is employed, focusing on a deep understanding of human experiences and the social construction of reality. The research findings indicate significant differences between live streaming production and conventional television production. The main differences lie in the stages of pre-production, production, and post-production.During the pre-production stage, the determination of themes, selection of sources, and preparation for live streaming are carried out. Challenges faced include difficulties in finding suitable schedules with sources and budget constraints.Subsequently, the production stage encompasses preparations for capturing footage and the actual filming process. Special equipment such as stable internet connections and appropriate broadcasting channels are required for live streaming production. Flexibility in the duration of the broadcasts becomes an advantage, but challenges such as unstable internet connections and adequate power supply also need to be considered.Once the production stage is completed, it is followed by the post-production stage, which involves tasks such as equipment setup and program evaluation. Unlike conventional television, live streaming broadcasts do not require editing processes as the content is aired directly. Common challenges include equipment adjustments, especially for outdoor programs. This research provides an understanding of the pre-production, production, and post-production processes of streaming television programs at Ceria TV. Despite the differences from conventional television, Ceria TV successfully manages its streaming production broadcasts. The study also offers insights into how local television can confront the challenges of competition in the evolving broadcasting industry.